Cross-Industry Innovation Processes Strategic Implications for Telecommunication Companies - Hahn, Tobias; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2015)
Based on multiple case study analysis, focusing on scalable service innovation, the present study provides a practical process model that shall serve telecommunication companies as a guideline while conducting strategic cross-industry innovation projects. The findings also pay attention to characteristics in cross-industry collaboration, organizational preconditions and strategic deliberations, and postulate propositions for present theoretical innovation process models. Content Context of cross-industry service innovation projects Grounded theory approach in multiple case study analysis Development of a practical innovation process model Propositions for theoretical innovation process models Target Groups Researchers and students in the fields of innovation management, organizational design, innovation strategy, corporate culture, alliances and partnering. Executives and consultants in corporate development and innovation management who seek to implement cross-industry innovation approaches. The Author Tobias Hahn obtained his doctorate at the Chair of Information and Communication Management at the Technische Universität Berlin. He currently works in the division of business transformation for a leading integrated telecommunications group.
Context of cross-industry service innovation projects -- Grounded theory approach in multiple case study analysis -- Development of a practical innovation process model -- Propositions for theoretical innovation process models.
Keywords: Economics; Industrial management; Business planning; Economics/Management Science; Innovation/Technology Management; Management/Business for Professionals; Organization/Planning.